UKHTY Enterprise : social media portfolio / Rosilah Abdul Rahim - Abdul Rahim, Rosilah (2018)
Based on this project, I was learn how to promote our product thru online and exposure in set up small business. This assignemnet also helping me to learn how to use facebook since I'm not familiar in using and posting in facebook. This is fast method in promoting our product. By using personal facebook, I'm start introduce our product and use social media as medium to gain profit. Facebook also one medium to get to know our customers and bridging relationship. Social media are important in nowdays.